Research care and teaching care research in the Faculty of Nursing at Universidad de Antioquia. Testimonies and legacies in 70 years of institutional life, 1950-2020 (2020)
ABSTRACT: The development of care research and its teaching in the Faculty of Nursing at Universidad de Antioquia cannot be understood outside the context in which it emerges and from the trajectory of its leading players. This is how this article will present a synthesis of the future of research, with its principal milestones and events in institutional history, in dialogue with the trajectories of four teaching nurses, protagonists of key moments in said history and living testimony of 70 years of institutional life. This panorama seeks to constitute a referent for strategic reflection, which inspires new generations to meet the research challenges and teach care research.